Sinisme dan Peringatan Moral dalam Puisi Hendak Jadi “Orang Besar?” Karya Bung Usman: Kajian Stilistika - Husna, Siti Asmaul; Suyanto, Edi; Agustina, Eka Sofia; Munaris, Munaris; Samhati, Siti (Institut Agama Islam Negeri Curup, 2025)
The poem Hendak Jadi “Orang Besar?” by Bung Usman is a literary work that delivers profound social criticism and moral admonition. This study adopts a stylistic approach using a descriptive qualitative method to analyze linguistic elements such as metaphors, irony, and satire that create a critical tone in the poem. Data were obtained through library research and analyzed based on the poet's choice of words, structure, and linguistic style to convey the intended message.The findings indicate that the poem Hendak Jadi “Orang Besar?” by Bung Usman employs metaphors to depict the negative impact of uncontrolled ambition, irony to highlight the emptiness of achievements without morality, and satire to critique selfish behaviors that disregard social values. The poem sharply illustrates the social realities of its time while inviting readers to reflect on values such as integrity, responsibility, and humanity in achieving true success. The moral messages conveyed in this poem remain relevant today, making it a meaningful social reflection worthy of appreciation.